2010
DOI: 10.1246/cl.2010.966
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and CO2 Absorption Properties of Single-phase Li2CuO2 as a CO2 Absorbent

Abstract: Synthesis and CO2 absorption properties of single-phase Li2CuO2 oxide were studied by X-ray powder diffraction and thermogravimetry. Samples of Li2CuO2 were prepared in solid state using Li2CO3 and CuO as starting reagents. A mixture of Li2CO3 and CuO was heated at temperatures of 600–1000 °C and then quenched to room temperature. From XRD, it was found that single-phase Li2CuO2 can be obtained by heat treatment at 680–685 °C with the quenching operation. The single phase was never obtained without quenching; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
2
25
2
Order By: Relevance
“…From this reaction, it is clear that the mass variation of CO 2 absorption increases with increasing x, showing agreement with the results of TG in Fig. 2, it was found that the equilibrium temperature of reaction (3) is lower than those of reactions (1) and (2). Since reaction (3) is reversible, from the results shown in Fig.…”
Section: October 2014supporting
confidence: 88%
See 1 more Smart Citation
“…From this reaction, it is clear that the mass variation of CO 2 absorption increases with increasing x, showing agreement with the results of TG in Fig. 2, it was found that the equilibrium temperature of reaction (3) is lower than those of reactions (1) and (2). Since reaction (3) is reversible, from the results shown in Fig.…”
Section: October 2014supporting
confidence: 88%
“…Therefore, it can be concluded that Ba 2 In 2 O 5 reversibly reacts with CO 2 by reaction (2). From Figs.…”
Section: October 2014mentioning
confidence: 76%
“…In this case, the maximum CO 2 chemisorbed was 28.3 wt%, and the thermogram shows the beginning of a CO 2 desorption process. Additionally, the amount of CO 2 captured by the Li 2 CuO 2 ball milled sample under these temperature and pressure conditions in a closed system is substantially higher than those observed in previous studies of Li 2 CuO 2 at atmospheric pressures between 30 and 350 C, [33][34][35][36] where the CO 2 chemical capture was not higher than 0.5 mmol g À1 . Similar results have been obtained in other lithium ceramics once their initial surface areas are improved.…”
Section: Resultscontrasting
confidence: 64%
“…According to the literature, Li 2 CuO 2 reacts with CO 2 as shown in reaction (1). [33][34][35][36] This sample presented a double chemisorption process, where the supercial and bulk processes were performed between 250 to 450 and 610 to 740 C, respectively. In this case, Fig.…”
Section: Resultsmentioning
confidence: 97%
“…These kinds of ceramics have shown to exhibit improved sorbent characteristics (Pfeiffer and Yun-Hang, 2010;Palacios-Romero and Pfeiíer, 2008). Matsukura et al (2010) reported that the single-phase Li 2 CuO 2 , obtained from solid-state reaction could absorb CO 2 equivalent to theoretical capacity (40.2 wt%) in the temperature range of 230e875 C.…”
Section: Lithium Cuprate (Li 2 Cuo 2 )mentioning
confidence: 99%